Green Synthesis of Luminescent Carbon Nanomaterials from Porphyridium cruentum Microalgae - Inês Chouzende; Alexandra Isabel Costa; Patrícia David Barata; Sónia Martins; Magda Cardoso Semedo; Fernando Manuel Henriques Cardoso; Maria Luísa Lobo; José Virgílio Prata (Medical Sciences Forum)
Microalgae (µAlgae) biomass was employed as a sustainable source for the synthesis of fluorescent carbon dots (μAlgae-CNDs) using a hydrothermal carbonization method and ethylenediamine (ED) as a nitrogen additive. The μAlgae-CNDs synthesized with a ratio of 0.64 of ED did not show cytotoxicity against non-tumor NIH 3T3 cells and sarcoma S180 cells, revealing some potential attractive properties for bioimaging.